2008
DOI: 10.1177/1012690208098545
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Anabolic Steroids and Other Prohibited Substances By Gym Enthusiasts in Cyprus

Abstract: The use of prohibited substances in sport does not solely concern athletes, but it is also quite common among other categories of the population: people who do not engage in competitive sports but use doping substances for a number of other reasons. This article is based on a survey that was administered to 532 people of both sexes, aged 14 years and above, in 22 gyms around Cyprus. The respondents engaged in one or more sports with a very small percentage (6%) participating in competitive sports. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 6 publications
1
19
0
2
Order By: Relevance
“…Prevalence studies can be ambivalent: they tackle public health issues and challenge researchers (Sagoe et al, 2014). Some authors show that in the background of epidemiological research, there is a risk of a moralistic approach to analyzing bodybuilders’ behavior (e.g., Kartakoullis et al, 2008; Christiansen et al, 2017), and the same risk exists with qualitative studies that analyze consumers’ discourses to understand how they normalize doping and risks (Monaghan, 2001; Stewart and Smith, 2008; Boardley and Grix, 2014). As a consequence, and bearing in mind the historical dimension of the definitions of the normal and the pathological (Canguilhem, 2012), we assume that considering extreme muscle solely as a pathology is too narrow, and we suggest the exclusion of moral judgments when analyzing the bodybuilding subculture.…”
Section: Apeds and Bodybuildingmentioning
confidence: 99%
“…Prevalence studies can be ambivalent: they tackle public health issues and challenge researchers (Sagoe et al, 2014). Some authors show that in the background of epidemiological research, there is a risk of a moralistic approach to analyzing bodybuilders’ behavior (e.g., Kartakoullis et al, 2008; Christiansen et al, 2017), and the same risk exists with qualitative studies that analyze consumers’ discourses to understand how they normalize doping and risks (Monaghan, 2001; Stewart and Smith, 2008; Boardley and Grix, 2014). As a consequence, and bearing in mind the historical dimension of the definitions of the normal and the pathological (Canguilhem, 2012), we assume that considering extreme muscle solely as a pathology is too narrow, and we suggest the exclusion of moral judgments when analyzing the bodybuilding subculture.…”
Section: Apeds and Bodybuildingmentioning
confidence: 99%
“…Its significance as a determinant of doping prevalence in amateur and recreational sport was shown in studies among gym users [1–2, 18] as well as for the use of anabolic androgenic steroids among university students ([3–9, 16], 14 more studies from the United States, cited in [5], 25 studies and three periodically conducted national youth surveys in the U.S., cited in [11], and three studies from Great Britain and Germany, cited in [10]). This effect was also shown in a special mixed sample of at-risk individuals [9], as well as in studies on doping substances in general among university students [17].…”
Section: Theoretical Assessment Of the Problem Areamentioning
confidence: 99%
“…Additionally studies have identified further social background variables such as social status [4, 7, 9, 12, 20, 21] and the intensity of involvement in sport [2, 7, 17, 19, 22] as determinants of doping. As we were not able to test hypotheses on these parameters due to the limited number of responses to our survey (see results section), we will not discuss these variables in detail.…”
Section: Theoretical Assessment Of the Problem Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are 39 National Sports Federations registered with the Cyprus Sports Organization and the Cyprus National Olympic Committee, and they are recognized members of the respective European and International Federations." (Kartakoullis et al, 2008) Sport in Cyprus has acquired special importance in Cypriot society over the years, and has become one of the most important social institutions on the island (Kartakoullis, 2006a). Recreational sport is also developing quickly, and a significant number of Cypriots are now engaged in this pastime.…”
Section: Introductionmentioning
confidence: 99%